Photolysis of four β‑lactam antibiotics under simulated environmental conditions: Degradation, transformation products and antibacterial activity - Timm, Alexander; Majewsky, Marius (The science of the total environment, 2019)
β‑Lactam antibiotics are among the most widely used antibiotics in human medicine and their effects on the aquatic environment - concerning bacterial resistance - are controversially discussed. This study focused on the photolysis of the four β‑lactam antibiotics - amoxicillin, ampicillin, penicillin V and piperacillin - under simulated environmental conditions. It was observed that all investigated β‑lactam antibiotics are photolytically degradable by simulated sunlight (1kW/m2) with half-lives between 3.2 and 7.0h. Structure elucidation of transformation products performed with liquid chromatography coupled to high resolution mass spectrometry showed that the hydrolysis of the β‑lactam ring is the primary transformation reaction, followed by the elimination of carboxylic and dimethyl thiazolidine carboxylic acid. Growth inhibition tests on Bacillus subtilis showed the loss of bactericide activity of irradiated solutions of amoxicillin, ampicillin and piperacillin, suggesting the transformation of the β‑lactam ring is responsible for the antibiotic effect. In contrast, the solutions of penicillin V did not show any decline of the antibacterial activity after photolytic degradation, probably due to the formation of still active epimers.